2019
DOI: 10.1186/s12871-019-0769-8
|View full text |Cite
|
Sign up to set email alerts
|

Functional fibrinogen (FLEV-TEG) versus the Clauss method in an obstetric population: a comparative study

Abstract: Background: Hemostasis is the dynamic equilibrium between coagulation and fibrinolysis. During pregnancy, the balance shifts toward a hypercoagulative state; however placental abruption and abnormal placentations may lead to rapidly evolving coagulopathy characterized by the increased activation of procoagulant pathways. These processes can result in hypofibrinogenemia, with fibrinogen levels dropping to 2 g/L or less and an associated increased risk of post-partum hemorrhage. The aim of the present study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…61,62 Studies have shown that TEG can rapidly detect changes in hemostasis, which is advantageous in the context of ongoing hemorrhage, but standard laboratory assays such as prothrombin time and activated partial thromboplastin time detected greater differences that correlated better with estimated blood loss. 63 Katz et al and Spasiano et al 64,65 compared the TEG method of measuring functional fibrinogen levels (FLEV) to the Clauss method, and reported that TEG-FLEV overestimates fibrinogen levels, which may lead to undertreatment or a delay in treatment. TEG has also been used to study coagulation changes in placental abruption, but further studies in this area are needed.…”
Section: Teg For Hemorrhage Managementmentioning
confidence: 99%
“…61,62 Studies have shown that TEG can rapidly detect changes in hemostasis, which is advantageous in the context of ongoing hemorrhage, but standard laboratory assays such as prothrombin time and activated partial thromboplastin time detected greater differences that correlated better with estimated blood loss. 63 Katz et al and Spasiano et al 64,65 compared the TEG method of measuring functional fibrinogen levels (FLEV) to the Clauss method, and reported that TEG-FLEV overestimates fibrinogen levels, which may lead to undertreatment or a delay in treatment. TEG has also been used to study coagulation changes in placental abruption, but further studies in this area are needed.…”
Section: Teg For Hemorrhage Managementmentioning
confidence: 99%
“…A further study including 34 healthy pregnant patients and 32 haemorrhaging pregnant patients suggested no significant differences in TEG maximum amplitude and functional fibrinogen maximum amplitude between these groups and that the TEG functional fibrinogen measurement overestimated the fibrinogen concentration in comparison with the Clauss method [66]. Sample sizes for both of the above studies, particularly of patients with PPH, were small and further data are required to confirm these findings.…”
Section: Resultsmentioning
confidence: 99%
“…This study used a TEG reagent that is designed to look at the intrinsic clotting pathway rather than isolate fibrinogen contribution to clot formation [42]. Recent studies looking at FLEV-TEG, designed to measure the contribution of fibrinogen, have raised concerns that it may overestimate fibrinogen levels and if used as a transfusion guide could lead to under treatment [43,44]. Small studies have described the benefit of using TEG in PPH [33,45] and TEG algorithms have been published based on normal values gained from healthy pregnant women [46].…”
Section: Point Of Care Coagulation Testsmentioning
confidence: 99%